ETHNIC TENSION IN KYRGYZSTAN IN THE POST-CONFLICT PERIOD: ETHNOSOCIOLOGICAL SURVEY RESULTS - CHOTAEVA, Cholpon (CENTRAL ASIA AND THE CAUCASUS, 2013)
The author analyzes the ethnocultural and psychological factors contributing to the continued ethnic tension in Kyrgyzstan in the post-conflict period. These factors figured prominently in the flare-ups of ethnic tension and continued ethnic strain. Dr. Chotaeva proceeds from the results of an ethnosociological survey carried out in five regions of Kyrgyzstan. The ethnocultural factors are related to various aspects of ethnic identity—the extent to which the family and close relatives affect ethnic self-identity and the degree to which the survey respondents were familiar with their ethnic history and followed ethnic traditions and customs in everyday life. The psychological factors were determined by the degree of trust the members of one ethnic group feel toward another. The sociological survey also included questions designed to identify the respondents’ civic identity, which directly depends on the degree to which the republic’s ethnic groups are integrated and which, on the other hand, is slowed down by ethnic and regional specifics. The continued ethnic tension has intensified an awareness of ethnic identity; however, the sociological survey demonstrated that a common civic identity still prevails over ethnic identity. The absolute majority of the respondents consider themselves to be citizens of Kyrgyzstan and are not contemplating emigration.